2001
DOI: 10.3310/hta5270
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of magnetic resonance imaging for investigation of the knee joint

Abstract: et al.The costeffectiveness of magnetic resonance imaging for investigation of the knee joint. Health Technol Assess 2001;5(27). Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA website (see opposite). NHS R&D HTA Programme T he NHS R&D Health Technology Assessment (HTA) Programme was set up in 1993 to ensure that high-quality research information on the costs, effectiveness and broader impact of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 71 publications
0
28
0
1
Order By: Relevance
“…After screening on title and abstract, 32 references remained. Then, screening the full-text article excluded 17 references, leaving 15 references for inclusion [11,[14][15][16][28][29][30][31][32][33][34][35][36][37][38]. Three RCTs were published twice [15,28,[35][36][37][38] and one trial had three different publications [11,33,34].…”
Section: Results Of the Search And Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening on title and abstract, 32 references remained. Then, screening the full-text article excluded 17 references, leaving 15 references for inclusion [11,[14][15][16][28][29][30][31][32][33][34][35][36][37][38]. Three RCTs were published twice [15,28,[35][36][37][38] and one trial had three different publications [11,33,34].…”
Section: Results Of the Search And Description Of Studiesmentioning
confidence: 99%
“…Several trials have focused on patients with other musculoskeletal disorders, of which two found significant results for the effect of imaging [14][15][16]. Clinicians generally assume that reassurance must follow from a confident statement that no disease has been found.…”
Section: Introductionmentioning
confidence: 99%
“…Any substantial economic impacts on society or on individuals are described in the text. Unit cost estimates were obtained from published literature, data from the Royal Orthopaedic Hospital in Birmingham, a recent survey of 11 NHS Trusts, 82 unpublished Swedish data, 77 as well as manufacturer and national sources (see appendix 5 footnotes). Mean costs were calculated when data were available for comparable procedures.…”
Section: Methods For Economic Analysismentioning
confidence: 99%
“…The prevalence or incidence of hyaline cartilage damage in knee joints is not known, partly because 2001; Vol. 5: No.…”
Section: Prevalence and Incidencementioning
confidence: 99%
See 1 more Smart Citation